PB-1-1 Teaching of Second Language Pronunciation from Perception of the Learners: A Case Study at Farah Higher Education Institute - Sultani, Mohammad Ebrahim; Anwari , Jawad; Matin, Fawad (Farah Research and Scientific Journal, 2024)
Since pronunciation instruction is one of several areas in the domain of instructed L2 acquisition that carries important potential to inform both theory and practice. It has drawn a lot of attention among the themes of research on pronunciation learning and teaching. However, research on current subject has yielded contradictory findings, despite numerous reports of notable advancements. This paper examines second language pronunciation instruction from the perspective of the language learner. Language models, instructional strategies, and activities are among the main topics being researched 35 third- and fourth-year English students at Farah Higher Education Institute participated in a survey to find out if such characteristics were present in the pronunciation classes and how much of an influence they had on students' learning. Significant tendencies were found after quantitative data were examined. The results show what the students think of the instructor and how they feel about the activities and methods of instruction that are offered. We will draw some conclusions so that L2 teachers might better assist their students in learning pronunciation.